Different influences of u-InGaN upper waveguide on the performance of GaN-based blue and green laser diodes - 梁锋;赵德刚;江德生;刘宗顺;朱建军;陈平;杨静;刘炜;李翔;刘双韬;邢瑶;张立群;李沫;张健 (Chinese physics B, 2017)
Performances of blue and green laser diodes（LDs） with different u-InGaN upper waveguides（UWGs） are investigated theoretically by using LASTIP. It is found that the slope efficiency（SE） of blue LD decreases due to great optical loss when the indium content of u-InGaN UWG is more than 0.02, although its leakage current decreases obviously. Meanwhile the SE of the green LD increases when the indium content of u-InGaN UWG is varied from 0 to 0.05, which is attributed to the reduction of leakage current and the small increase of optical loss. Therefore, a new blue LD structure with In（0.05） Ga（0.95）N lower waveguide（LWG） is designed to reduce the optical loss, and its slope efficiency is improved significantly.